The effect of stand-off distance on damage to clamped square steel plates under enclosed explosion. (June 2020) - Li, X.D.; Yin, J.P.; Zhao, P.D.; Zhang, L.; Xu, Y.X.; Wang, Q.; Zhang, P.
Highlights: A combination of enclosed explosion tests were carried out in a steel box and fully clamped square plates showed less deflection at smaller stand-off distances, which was a phenomenon different from open explosions. The relationship between deflection of the plate and stand-off distance is discussed. Four failure modes were observed and theories of each failure mode were analyzed. Fully clamped square plates showed less deflection at smaller stand-off distances under enclosed explosion. Abstract: The deformation and failure modes of fully clamped square plates at different stand-off distances were investigated using a combination of enclosed explosion tests and numerical simulations. The research shows that the stand-off distance is an important parameter affecting the deformation and failure of target plates. Fully clamped square plates showed less deflection at smaller stand-off distances, which was a phenomenon different from open explosions, under the experimental conditions presented in this paper. Causes of this phenomenon were analyzed by finite element method and the relationship between deflection of the plate and stand-off distance is discussed. Four failure modes were observed and theories of each failure mode were analyzed. Finally, the scaled distance parameter was introduced and a failure mode map of the fully clamped square steel plate under enclosed explosion was plotted as a function of scaled distance.